Diminishing Arctic sea ice extent and its effects on atmospheric circulation in the Northern Hemisphere in different seasons - Salokivi, Jouni (Helsingin yliopisto, 2019)
The aim of this Master’s thesis is to study the local and remote effects of the Arctic sea ice decline on atmospheric circulation in the Northern Hemisphere in the Eurasian continent. The climate in the Arctic area has been getting warmer due to global warming and the Arctic Amplification enhancing its effect. This has caused a decline in the Arctic sea ice extent and thickness, and a lengthening of the melting season. Local effects of the sea ice decline have been the rise in surface air temperature, increase in sensible and latent heat fluxes from the ocean, increase of moisture in the troposphere and therewith increase in cloudiness and precipitation. This has also caused more turbulence and smaller stratification in the lower troposphere, and an increased boundary layer thickness. A warmer Arctic area and a consequent sea ice decline has decreased the meridional pressure field height gradient and thereby the westerly geostrophic wind in the upper troposphere. The jet stream trajectory has become more meridional and meandering, which resembles the negative phase of the NAO/AO index. This has advected in winter warm air to the Pole and cold air to the Eurasian continent. Blocking highs over the Atlantic and Siberia have further advected cold air to the continent with cold and snow-rich winters as a result. In China the effect has been a more stable lower troposphere with less cyclone activity in winter whereas in spring the sea ice decline has brought lower temperatures and a weakening of the East Asian Jet. In summer Europe has experienced higher precipitation and eastern Asia a strengthening of the Eastern Asia Summer Monsoon. Different studies have suggested different mechanisms for this. Effects in autumn have been mainly the same as in winter, with weather patterns similar to the negative phase of the NAO/AO index. As a conclusion, it was found in the study that the decline in Arctic sea ice has had quite expected, better understood local effects. The results on remote effects are still partly ...